Symbol Reinterpretation as a Motivation for Integration of Chinese Muslim Ethnic Identity - Ghofar Taufik; Asep Saeful Muhtadi; Munir Munir; Dody S. Truna (UIN Sunan Gunung Djati, 2022)
This study focuses on research with a phenomenological approach regarding the symbolic meaning of the ethnic Chinese Muslim identity at the Lautze 2 Mosque in Bandung City, which focuses on concluding the meaning of ethnic symbols in Chinese New Year as a means to integrate in the form of friendship and participation with the Chinese extended family; the meaning of Ethnic Symbols in Feng Shui which is still used and believed among Chinese Muslims; the meaning of the ethnic symbols in the lion dance which is still preserved as an art in various Chinese performances and endeavors; and the meaning of ethnic symbols in the Lucky Cat, which is still practiced in some Chinese Muslim circles, and is valued as part of the wisdom of the Chinese ancestor.Â The study attempted to remain integrated with a more significant initial ethnic identity. For Chinese Muslims, family ties or relatives are essential in maintaining friendly relations, and believing Islam is the teachings of rahmatan lil 'alamiin. In addition, there is a reinterpretation of the symbols of Chinese ethnicity as a form of strengthening the identity of the Chinese Muslim ethnic group. This study can be used as theoretical knowledge in the form of theoretical conception to enrich the theories of the study of religions to assess the religious phenomenon associated with symbols of ethnic identity and religious identity, even acculturation between newcomers and natives. In addition, practically from the research, it is suggested to be an academic consideration for various government policies to build inter-religious harmony and harmony between ethnicities and groups, especially regarding religious conversion and belief and taboo issues in Indonesia.